Assessing the Spiritual Leadership of Students: An Equanimity Study. Issue 2 (2nd April 2016) - Rozeboom, David; Frohardt, Russell; Carroll, Claudia; Sullivan, Tom; Phelps, Nick; Trevino, Nicole; Blair, David; Brown, Christy; Puglisi, James
Abstract: Researchers at a regional western university surveyed undergraduate students on the extent to which they identified themselves as spiritual leaders and, in particular, as having the quality of equanimity, one component of spiritual leadership. The results illustrate the role that equanimity plays in the development of a student's leadership capacity. Implications for student affairs practitioners are discussed.